1981
DOI: 10.1136/bjo.65.8.575
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of loss of vision in the healthy eye in amblyopia.

Abstract: SUMMARY In Finland during the 20-year period 1958-78 35 patients with amblyopia lost the vision of the healthy eye. In more than 50% the cause was traumatic. The incidence of the loss of the healthy eye was 1'75+0-30 per thousand. During the same period in Finland the overall blindness rate of children was 0 11 per thousand and of adults aged 15-64 years 0-66 per thousand. For the amblyopic patient the risk of becoming blind is markedly higher than for the general population.It is generally thought that ambly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0
7

Year Published

1984
1984
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(84 citation statements)
references
References 2 publications
0
76
0
7
Order By: Relevance
“…The number of severe eye injuries among the Omani children is relatively high (Lithander, in preparation) and the risk of losing the healthy eye is increased compared to the risk of losing the amblyopic eye in an accident, as shown by Tommila & Tarkkanen in 1981. Increased prevalence of blindness in the population is still a reality in this part of the world.…”
Section: Discussionmentioning
confidence: 99%
“…The number of severe eye injuries among the Omani children is relatively high (Lithander, in preparation) and the risk of losing the healthy eye is increased compared to the risk of losing the amblyopic eye in an accident, as shown by Tommila & Tarkkanen in 1981. Increased prevalence of blindness in the population is still a reality in this part of the world.…”
Section: Discussionmentioning
confidence: 99%
“…Early identification and treatment of strabismic children may prevent amblyopia 7 . The strabismus child with amblyopia has a significantly higher risk of becoming blind by losing vision in the non-amblyopic eye, due to trauma or disease 8,9 . In the developed countries, many parents notice squint early in their babies and present early to the ophthalmologists unlike in the developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…52 While the debate on preschool vision screening continues, primary screening backed up by secondary orthoptic/optometric assessment has been shown to substantially decrease the number of inappropriate referrals to hospital clinics. 33,51,[53][54][55][56][57][58] Where this occurred, only 14% were referred to the hospital clinic, of whom 76% were referred back to the community for subsequent full or partial management. 54 Such schemes have also demonstrated that children are referred earlier for treatment (average age decreased from 6.6 years to 5 years) and that the relationship between social deprivation and the age of presentation of asymptomatic amblyopia is abolished.…”
Section: Discussionmentioning
confidence: 99%